Hypokalemic Periodic Paralysis (HPP) as the Initial Presentation of Uncontrolled Non-Ketotic Diabetes: A Case Report Highlighting the Importance of Screening for Maturity-Onset Diabetes of the Young (MODY) in an Adolescent Female - Rahayuning Utami; Imarra Nusaibah (The International Journal of Medical Science and Health Research, 2025)
Introduction Hypokalemic Periodic Paralysis (HPP) constitutes a rare subgroup of neuromuscular channelopathies characterized by sudden, reversible episodes of flaccid muscle weakness that coincide with profound hypokalemia (serum potassium <3.5 mmol/L). While the majority of HPP cases are attributed to inherited familial disorders (FPP), secondary forms are recognized, often precipitated by hormonal or metabolic imbalances. The co-occurrence of severe HPP manifesting as the primary acute complication of uncontrolled non-ketoacidotic diabetes is exceptionally uncommon and poses a significant diagnostic and therapeutic challenge, especially when the clinical picture suggests an underlying monogenic etiology, such as Maturity-Onset Diabetes of the Young (MODY). Case Illustration This report presents a detailed account of a 19-year-old female (Nn. R) who presented to the emergency department on November 7, 2025, with acute and complete flaccid paralysis of the lower extremities (Motor Strength 2/2). Initial biochemical analysis revealed life-threatening hypokalemia (Serum K+=1.50 mEq/L) concomitant with severe, non-ketotic hyperglycemia (Glucose 451 mg/dL, Keton 0.1). The presence of QT prolongation on the electrocardiogram (ECG) indicated high cardiac risk and necessitated immediate admission to the Intensive Care Unit (ICU) for aggressive intravenous potassium replacement and continuous cardiac monitoring. Complete motor function was successfully restored following the normalization of potassium levels (K+ = 3.81 mEq/L) over a six-day hospitalization period. Discussion The rapid and complete recovery of muscle strength upon correction of the potassium deficit confirmed the diagnosis of secondary HPP induced by a massive transcellular shift. This shift was triggered by the potent Na+/K+-ATPase activity stimulated by acute metabolic stress (hyperglycemia). Significantly, the patient's presentation—young age, absence of ketoacidosis, and the high efficacy observed upon clinical transition to long-term sulfonylurea (Glikuidone 30 mg) therapy at discharge—strongly suggests an underlying HNF1A- or HNF4A-MODY phenotype. This clinical finding underscores the utility of recognizing atypical diabetic presentations to ensure appropriate, precision-guided long-term care. Conclusion This case emphasizes the necessity of prompt, aggressive, and strategically administered potassium management in severe HPP to avert fatal cardiac events. Furthermore, the report highlights the critical diagnostic pathway required to identify underlying MODY in patients with HPP and atypical diabetic features, ensuring the selection of appropriate therapy (sulfonylureas) to prevent recurrent paralytic episodes.